2017
DOI: 10.1080/09638288.2017.1387614
|View full text |Cite
|
Sign up to set email alerts
|

The tailored activity program (TAP) to address behavioral disturbances in frontotemporal dementia: a feasibility and pilot study

Abstract: This study demonstrates the potential for using an activity-based intervention such as the Tailored Activity Program in frontotemporal dementia. Service providers should recognize that while people with frontotemporal dementia present with challenging issues, tailored therapies may support their function and reduce their behavioral symptoms. Implications for rehabilitation The Tailored Activity Program is an occupational therapy based intervention that involves prescribing personalized activities for behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 65 publications
4
70
2
1
Order By: Relevance
“…TAP-VA also benefited caregivers by reducing distress with behavior. Results are consistent with those of other TAP trials (initial pilot, TAP-hospital, 22 TAP Brazil, 23 TAP-Australia), 24 extending reported benefits to pain and functional dependence.…”
Section: Discussionsupporting
confidence: 89%
“…TAP-VA also benefited caregivers by reducing distress with behavior. Results are consistent with those of other TAP trials (initial pilot, TAP-hospital, 22 TAP Brazil, 23 TAP-Australia), 24 extending reported benefits to pain and functional dependence.…”
Section: Discussionsupporting
confidence: 89%
“…This preliminary study replicates in part previous studies testing the TAP in-home version 5,18,20,28 and nonpharmacological interventions in reducing hallucinations, 29 agitation, [30][31][32] anxiety, 30 and motor disturbance. 33 Brodaty and Burns 34 report there are NPS that are more responsive to nonpharmacological interventions when compared with hallucinations and delusions.…”
Section: Discussionsupporting
confidence: 80%
“…Evidence suggests that individuals with dementia can effectively engage in activities when these activities are adapted to meet the individual's abilities. 17,18 Gitlin et al 5,16,19,20…”
mentioning
confidence: 99%
“…Fifteen studies14 15 17 31–42 were eligible for inclusion from a total of 9737 articles identified from database searches and other sources (see online supplementary file 4: PRISMA flow diagram). A number of these studies reported the results of different outcomes for the same study in separate reports.…”
Section: Resultsmentioning
confidence: 99%